Application of Ethnomathematics in Tumpi-Tumpi Food for Math Learning - Ulfa Ainul Qalbi; Muhammad Yusran Arif; Nirfayanti Nirfayanti (RANGE: Jurnal Pendidikan Matematika, 2025)
This research aims to apply the concept of ethnomathematics in mathematics learning through traditional Bugis-Makassar food, namely Tumpi-Tumpi. Ethnomathematics refers to understanding how mathematical concepts can be found in local cultures. The method used in this research is a literature study to review relevant literature on ethnomathematics in Bugis-Makassar typical food, especially Tumpi-Tumpi. The data obtained were then systematically synthesized and analyzed within a systematic literature review (SLR) framework to identify trends, gaps, and existing understandings regarding the application of mathematical concepts in traditional foods such as Tumpi-Tumpi. The results showed that Tumpi-Tumpi contains mathematical elements that can be used as teaching tools, such as the pattern and size of the food. This application of ethnomathematics can increase students' engagement in mathematics learning by linking mathematical concepts to their local culture. These findings highlight the importance of integrating ethnomathematics into mathematics learning through Tumpi-Tumpi to not only enrich students' learning experiences that are more meaningful and relevant, but also strengthen their cultural identity and understanding of mathematics in everyday contexts.